Prevalence of malaria in Woreta town, Amhara region, Northwest Ethiopia over eight years - Amir Alelign; Zinaye Tekeste; Beyene Petros (BMC, 2018)
Abstract Background Data on trends in malaria prevalence is significant to assist efforts in the control and prevention of the disease. This retrospective study was, therefore, aimed to determine the prevalence of malaria in Woreta town, northwestern Ethiopia over 8 years. Methods A retrospective study was conducted in Woreta town, northwestern Ethiopia, from November to January 2013. Eight years (2005 to 2012) health center record of malaria cases was reviewed. Odds ratio (OR) was used to determine trend in malaria prevalence with respect to age, sex and Plasmodium species. P-values less than 0.05 were considered to be statistically significant. Results From 2005 to 2012, a total of 102,520 suspected cases of malaria were reported at Woreta health center. Of these, 33,431 (32.6%) were microscopically confirmed to be positive for the disease. Among these positive cases, 17,700 (52.9%) and 15,731 (47.1%) were males and females, respectively. Children less than 5 years old were 1.3 times more likely to be infected by malaria than those with 5-15 years ([OR]; 1.3, 95% confidence interval [CI]; 1.26-1.34, p < 0.001). There was higher percentage (69.7%) of Plasmodium falciparum infection than Plasmodium vivax (26.5%); and the difference was statistically significant (p < 0.05). There was fluctuation in yearly malaria prevalence with a minimum of 7% in 2008 and maximum of 47% in 2005. Conclusions The present study revealed that malaria continued to be one of the major public health problems in Woreta town, northwest Ethiopia. Moreover, there was no successive yearly reduction in its prevalence. Therefore, efforts are required to reduce the disease burden through continuous monitoring and evaluation of control measures in the study area.